2021
DOI: 10.3168/jds.2020-19277
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of a tail-activity measuring device for calving prediction in dairy cattle

Abstract: Efficient calving surveillance is essential for avoiding stillbirth due to unattended dystocia. Calving sensors can help detect the onset of parturition and thus ensure timely calving assistance if necessary. Tail-raising is an indicator of imminent calving. The objective of this study was to evaluate a tail-mounted inclinometer sensor (Moocall Ltd., Dublin, Ireland) and to monitor skin integrity after sensor attachment. Cows (n = 157) and heifers (n = 23) were enrolled at 275 d post insemination, and a senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…In contrast, the fixation of the CalveSense device with an adhesive and tape did not cause any swellings to the animals' tails. We thus reinforce that swelling of the tail due to calving sensor fixation is unacceptable (see [8,10]).…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…In contrast, the fixation of the CalveSense device with an adhesive and tape did not cause any swellings to the animals' tails. We thus reinforce that swelling of the tail due to calving sensor fixation is unacceptable (see [8,10]).…”
Section: Discussionsupporting
confidence: 72%
“…As also reported in Lind and Lindahl [10] and Voss [8], we point out that attaching a sensor with a ratchet (as is the case with the Moocall sensor) to an animal's tail is challenging, even after long-time practice. The two studies reported swellings to the tail in 17% [8] and 87% [10] of animals to which a Moocall sensor was attached, and frequent dropping off the tail. Both these problems were also experienced on the dairy research and demonstration farm.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations